1999
DOI: 10.1038/sj.bjc.6690706
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical regulation of Bcl-2 family proteins by 17β-oestradiol in human breast cancer cells MCF-7

Abstract: Summary Tumorigenesis is related to the dysregulation of cell growth or cell death pathways. Hence, elucidation of the mechanisms involved in the modulation of pro-or anti-apoptotic proteins is important in furthering understanding of breast cancer aetiology and may aid in designing prevention and treatment strategies. In the present study, we examined the role of 17β-oestradiol on the regulation of apoptosis in the breast cancer cell line MCF-7. Using multi-probe RNAase protection assays, we found changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 31 publications
4
43
1
Order By: Relevance
“…Furthermore, c-Myc-induced apoptosis appeared independent to the well-established ability of c-Myc to repress Bcl2 family genes (Maclean et al, 2003), because no consistent effect of c-Myc on expression of Bcl2 (BCL2), Bcl-xL (BCL2L1) and Mcl1 (MCL1) transcripts was observed in hES cells ( Figure 5b). Treatment of 4OHT slightly, but c-Myc independently, affected Bcl2 expression in cells expressing either control vector or c-MycER, because estrogen has been shown to be capable of regulating Bcl2 expression (Leung and Wang, 1999). Thus, these data show that sustained activation of c-Myc upregulates some cell cycle regulators but not anti-apoptotic regulators in hES cells, and suggest that induction of cyclin family genes might not be sufficient to promote hES cell proliferation.…”
Section: Apoptosis Of Hes Cells Induced By Sustained C-myc Activationmentioning
confidence: 66%
“…Furthermore, c-Myc-induced apoptosis appeared independent to the well-established ability of c-Myc to repress Bcl2 family genes (Maclean et al, 2003), because no consistent effect of c-Myc on expression of Bcl2 (BCL2), Bcl-xL (BCL2L1) and Mcl1 (MCL1) transcripts was observed in hES cells ( Figure 5b). Treatment of 4OHT slightly, but c-Myc independently, affected Bcl2 expression in cells expressing either control vector or c-MycER, because estrogen has been shown to be capable of regulating Bcl2 expression (Leung and Wang, 1999). Thus, these data show that sustained activation of c-Myc upregulates some cell cycle regulators but not anti-apoptotic regulators in hES cells, and suggest that induction of cyclin family genes might not be sufficient to promote hES cell proliferation.…”
Section: Apoptosis Of Hes Cells Induced By Sustained C-myc Activationmentioning
confidence: 66%
“…It is now established that E 2 induces transcription of the BCL2 gene and increases expression of BCL2 protein, which exerts antiapoptotic action in many cell types (Huang, 1997;Dong et al, 1999;Leung and Wang, 1999). In addition to genomic actions, E 2 has been known to exert rapid, likely nongenomic actions both in the whole animal and in cultured cells (Szego, 1974;Huang, 1997;Razandi et al, 2000a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Estrogens, in particular 17-␤ estradiol (E 2 ), are well-characterized mitogens for mammary tissues and epithelial cells of the female reproductive tract. Whereas estrogens exert antiapoptotic influence in neurons (Zhang et al, 2001), epithelial cells of the female reproductive tract (Leung and Wang, 1999;Choi et al, 2001), immune system, blood cells, and endothelial cells (Bynoe et al, 2000;Haynes et al, 2000), they also have significant apoptotic effects on certain classes of bone-derived cells (Hughes et al, 1996;Kameda et al, 1997) and some immune system cells (Zajchowski and Hoffman-Goetz, 2000;Okasha et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies follow different procedures with regard to 'antigen exposing' and principles of incubation with antibodies, as well as in microscopic assessment criteria. Studies that analyzed the expression of ERs and other markers in breast cancer usually lacked information as to whether or not the cases analyzed included tumors without chemotherapy or tumors treated with pre-operative chemotherapy, and the extent thereof (20)(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…No relationship was observed between ER expression and Bak. Other studies have shown that estrogens increase Bcl-2 protein expression in epithelial breast cells (21) and in certain breast cancer lines, thereby lengthening the life of these cells (22). Berardo et al (23) showed that a high Bcl-2 expression was associated with favorable prognostic factors, such as positive ER status, a low fraction of cells in the S-phase of the cell cycle and a low number of lymph nodes with neoplastic metastases.…”
Section: Comparison Of Markers P-value R ----------------------------mentioning
confidence: 99%